Doctors have an ethical obligation to ask patients about food insecurity: what is stopping us?. Issue 10 (14th July 2021) - Knight, Jessica Kate; Fritz, Zoe
Abstract : Inadequate diet is the leading risk factor for morbidity and mortality worldwide. However, approaches to identifying inadequate diets in clinical practice remain inconsistent, and dietary interventions (on both individual and public health policy levels) frequently focus on facilitating 'healthy choices', with limited emphasis on structural constraints. We examine the ethical implications of introducing a routine question in the medical history about ability to access food. Not collecting data on food security means that clinicians are unable to identify people who may benefit from support on an individual level, unable to consider relevant dietary risk factors for disease and disease progression and unable to monitor population trends and inequalities in dietary access in order to design effective policy interventions. We argue that the current lack of routine screening for food insecurity is inconsistent with our approach to other health behaviours (eg, smoking and alcohol use), as well as with doctors' frequent informal role as gatekeepers to the food aid system, and recent calls for governmental action on food insecurity and health inequalities from individual clinicians and professional bodies. Potential ethical barriers to asking patients about food security are addressed, including concerns about stigma, limiting autonomy, fair resource allocation, unclear professional remits and clinicians' ability to offer effective interventions. We suggest that there is an ethical imperative for doctors to ask patients about their ability to access healthy food. Gathering this data provides a valuable first step in re-framing the social determinants of health as modifiable risks, rather than inevitable inequities.